HIV/AIDS stigma, perceived social support and mental health problems among HIV/AIDS children: a mediation analysis. Issue 1 (2nd January 2023) - Singh, Varsha; Anupriya,; Verma, Shikha; Lata, Swaran
ABSTRACT: Extensive research on HIV/AIDS stigma is conducted on adults, but it cannot be equated with the experiences of children. This makes it obvious to develop an inclusive research on child experience of HIV/AIDS stigma. For that reason, the present study investigates the relationship among HIV/AIDS stigma, perceived social support and mental health problems in HIV/AIDS children. A sample of 90 HIV/AIDS children aged 10–18 years from Moti Lal Nehru Hospital, Allahabad, Uttar Pradesh, India, were recruited. Participants were assessed on HIV/AIDS stigma, perceived social support and mental health problems. Descriptive statistics, correlational and regression analysis and mediation analysis were performed to accomplish the purpose of the study. Correlational analysis makes it evident that perceived social support is prominently negatively correlated with HIV/AIDS stigma ( r (88) = −.670, p < 0.01) whereas mental health problems ( r (88) = .753, p < 0.01) was significantly positively correlated with HIV/AIDS stigma. Taking hierarchical regression analysis into consideration, it was found that the perceived social support significantly contributed to 33.2% variance in HIV/AIDS stigma and HIV/AIDS stigma contributed to 45.9% variance in mental health problems. Results of the mediation analyses validate the mediating role of HIV/AIDS stigma in the association between perceived social support and mental health problems ( β = −0.27, CI = −.33 to −.034, p = .017). These findings contribute to empirical evidence about psychological predictors and the observable consequences of HIV/AIDS-related stigma.